Effectiveness of Agarwood Formation Using a Fungal Consortium on Three Stem Diameter Sizes of Aquilaria malaccensis Lamk. in Banyuwangi - Humaera, Apra; Sasmuko, Sentot Adi; Muspiah, Aida; Pradita, I Made Nanda; Mulyaningsih, Tri (Universitas Sam Ratulangi, 2025)
Agarwood is a wood containing fragrant resin produced as a response of tree defense against disease. One of the artificial techniques that can be used for agarwood induction is inoculation, which is a technique of inserting pathogens (inoculants) into the stem such as fungi as a disease to accelerate the stimulation of agarwood formation. This study aims to analyze the size of the stem diameter against the length of infection propagation, the thickness of aromatic resin propagation, resin color and anatomical characteristics of agarwood to see the distribution of resin in the tissue, after being induced by a fungal consortium. Induction in this study was carried out on 3 sizes of tree trunk diameters (10 cm, 15 cm, and 20 cm) with 3 repetitions. Data were analyzed using analysis of variance (ANOVA) and qualitative descriptive for resin anatomy and color. The longest propagation of aromatic resin was obtained on a stem with a diameter of 15 cm. The aromatic resin that produced the darkest color was obtained from a stem with a diameter of 10 cm. The longest infection propagation was obtained on a stem with a diameter of 20 cm.The distribution of aromatic resin in the tissue accumulates in the pith rays, interxilary phloem, trachea, and tracheids.